2021
DOI: 10.1111/ajco.13659
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of intraperitoneal paclitaxel in combination with intravenous cisplatin and oral capecitabine in patients with advanced gastric cancer and peritoneal metastases (IPGP study)

Abstract: Aims Gastric cancer with peritoneal involvement has a poor prognosis. Intraperitoneal (IP) paclitaxel has shown promising results in these patients. However, this approach has only been studied in the Asian population, and in combination with S‐1. We investigated the maximum tolerated dose of IP paclitaxel, with a standard chemotherapy combination, in the Australian population. Methods The study of the population included metastatic human epidermal growth factor receptor 2 (HER2) negative gastric adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…histology and/or cytology Paclitaxel at days 1 and 8 in 3-week cycles Paclitaxel + S-1 30 mg/m 2 20 mg/m 2 Febrile neutropenia grade 3, diarrhea grade 3 Kurita et al, 2011 [ 89 ] 4 18 Pos. histology and/or cytology Paclitaxel at days 1 and 14 in 4-week cycles S-1 90 mg/m 2 80 mg/m 2 Leukocytopenia grade 3 Vatandoust et al, 2022 [ 90 ] 4 15 Pos. histology Paclitaxel at days 1 and 8 in 3-week cycles Cisplatin + capecitabine Not reached 30 mg/m 2 Small bowel obstruction grade 3, febrile neutropenia grade 3 Kobayashi et al, 2020 [ 91 ] 4 9 Pos.…”
Section: Results Of Intraperitoneal Chemotherapy For Unresectable Per...mentioning
confidence: 99%
See 1 more Smart Citation
“…histology and/or cytology Paclitaxel at days 1 and 8 in 3-week cycles Paclitaxel + S-1 30 mg/m 2 20 mg/m 2 Febrile neutropenia grade 3, diarrhea grade 3 Kurita et al, 2011 [ 89 ] 4 18 Pos. histology and/or cytology Paclitaxel at days 1 and 14 in 4-week cycles S-1 90 mg/m 2 80 mg/m 2 Leukocytopenia grade 3 Vatandoust et al, 2022 [ 90 ] 4 15 Pos. histology Paclitaxel at days 1 and 8 in 3-week cycles Cisplatin + capecitabine Not reached 30 mg/m 2 Small bowel obstruction grade 3, febrile neutropenia grade 3 Kobayashi et al, 2020 [ 91 ] 4 9 Pos.…”
Section: Results Of Intraperitoneal Chemotherapy For Unresectable Per...mentioning
confidence: 99%
“…However, a retrospective analysis on intraperitoneal paclitaxel showed that the type of systemic chemotherapy did not influence overall survival [86]. In Phase I studies, intraperitoneal paclitaxel in combination with several types of systemic chemotherapy resulted in recommended doses between 20 and 80 mg/m 2 , depending on the frequency of administration [87][88][89][90][91][92][93]. The most common dose-limiting toxicities (DLTs) were hematological disorders (mostly neutropenia) or gastro-intestinal toxicities such as diarrhea or vomiting.…”
Section: Gastric Cancermentioning
confidence: 99%